(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to study the relationship between the depth of mathematical knowledge and information processing for secondary school students,In order to verify the goal, the researchers adopted the descriptive approach in line with the nature of the research, and the following null hypothesis was formulated:There is no statistically significant correlation at the significance level (0.05) between the depth of mathematical knowledge and information processing for the fifth literary grade students.The research community, represented by the literary fifth grade students in the Rusafa 2nd, Education Directorate, was identified, and the sample was chosen in a stratified random manner, as it consisted of (400) students and the construction of the two research tools are the Mathematical Knowledge Depth Test and the Information Processing and Application Test on the Sample, statistical analyzes were conducted for the two test items, to ensure the psychometric properties, and the use of appropriate statistical tools and package (spss) to analyze the results of the application of the two tests, which resulted in the existence of a correlation between the depth of mathematical knowledge and information processing.In light of the results of the research, several recommendations were made, most notably the interest in ways and methods that can develop the levels of depth of mathematical knowledge and information processing among secondary school students in general, as well as the diversity of activities given to students of the fifth literary grade, which develop their depth of mathematical knowledge and information processing skills.